Kondisi Konsentrasi Belajar Anak Usia Dini di Taman Kanak-Kanak X - Wan Chalidaziah (Aṭfāluna: Journal of Islamic Early Childhood Education, 2018)
Learning concentration is an important component in learning process, with a high concentration of learning in each child, then able to support the child to be ready to further education. This research aims to describe how the condition of learning concentration is early childhood before entering elementary school age. The method used in the study was a descriptive research method accompanied by a short interview with a class teacher at Taman Kanak-Kanak X. Sample research amounted to 25 children of early childhood using NST (Nijmeegse Schoolbekwaamheid Test) as a research instrument. The results of this study are generally the early childhood learning concentration is on good criteria and still there is a concentration of learning children who are in the criteria of doubt and there are also some children who have a concentration criteria Learning is not ready to shrink further education in elementary school. The author suggests that further research can further investigate the proper way to improve the concentration of early childhood in Taman Kanak-Kanak X.